Paciente de sexo femenino de 22 años de edad con enfermedad celiaca. - Huaigua Chiluiza, Alex Paul (2021)
Celiac disease is an autoimmune clinical condition characterized by gluten intolerance in people. This clinical case is about a female patient who is 22 years of age who goes to medical consultation for having symptoms of diarrhea, colic, pain and bloating, to anamnesis states that symptoms were triggered after gastroenteritis, suspected inflammatory bowel disease are sent biochemical tests themselves that test positive for celiac disease, confirming the diagnosis with a biopsy that determined MARSH 1-type celiac disease. The objective of this clinical case is to provide a nutritional plan according to the nutritional and pathological needs of the patient that entails the improvement of symptomatology. Throughout the development it is determined that the patient is in a normal nutritional state, there is no significant weight loss and no nutritional deficiencies, so a diagnosis is established and treatment is provided by a gluten-free nutritional plan, as well as when monitoring for the following 2 weeks, it finally manages to improve the symptomatology described at the beginning.